Variable broad lines and outflow in the weak blazar PBC J2333.9−2343. Issue 4 (18th May 2018) - Hernández-García, L; Vietri, G; Panessa, F; Piconcelli, E; Chavushyan, V; Jiménez-Andrade, E F; Bassani, L; Bazzano, A; Cazzoli, S; Malizia, A; Masetti, N; Monaco, L; et al.
ABSTRACT: PBC J2333.9−2343 is a peculiar active nucleus with two giant radio lobes and a weak blazar-like nucleus at their centre. In this work we show new optical, ultraviolet (UV), and X-ray data taken from the San Pedro Mártir telescope, the New Technology Telescope, NTT/EFOSC2, and the Swift /XRT satellite. The source is highly variable at all frequencies, in particular the strongest variations are found in the broad Hα component with a flux increase of 61±4 per cent between 2009 and 2016, following the X-ray flux increase of 62±6 per cent between 2010 and 2016. We also detected a broad Hβ component in 2016, making the optical classification change from type 1.9 to type 1.8 in 1 yr. We have also detected a broad component of the [oiii ]λ5007 line, which is blue-shifted and of high velocity, suggesting an origin from a highly disturbed medium, possibly an outflow. The line flux variability and broad widths are indicative of a jet that is, at least in part, responsible for the ionization of the broad line region (BLR) and narrow line region (NLR).